Draft Annual Plan 1993-94 Part II - Plan Proposals in Detail Government of Goa - Planning Commission (Planning Commission, 1993)
Emphasis will be given to increase area and production of different pulse crops like cowpea, Mung, Urid as well as the local variety of Alsando. The thrust will be to increase per unit area production by providing incentives as follows: (a) To provide custom service at 50% subsidised rate to individuals group of farmers, specially for quick and timely cultivation soon after harvest of Kharif paddy, thus helping farmers to grow pulses on residual soil moisture during rabi season.
Government of Goa, Directorate of Planning, Statistics and Evaluation